Factorize by Grouping The Terms

Factorize by grouping the terms (two or more) means that we need to group the terms which have common factors before factoring. 


Method to factorize by grouping the terms:

(i) From the groups of the given expression a common factor can be taken out from each group.

(ii) Factorize each group

(iii) Now take out the factor common to group formed.

Now we will learn how to factorize by grouping two or more terms.

Solved examples to factorize by grouping the terms:

1. Factorize grouping the following expressions:

(i) 18a3b3 - 27a2b3 + 36a3b2

Solution:

18a3b3 - 27a2b3 + 36a3b2

= 9a2b2(2ab – 3b + 4a)


(ii) 12x2y3 - 21x3y2

Solution:

12x2y3 - 21x3y2

= 3x2y2(4y - 7x)


(iii) y3 - y2 + y - 1

Solution:

y3 - y2 + y - 1

= y2(y - 1) + 1(y - 1)

= (y - 1) (y2 + 1)


(iv) axy + bcxy – az – bcz

Solution:

axy + bcxy – az – bcz

= xy(a + bc) – z(a + bc)

= (a + bc) (xy – z)


(v) x2 - 3x – xy + 3y

Solution:

x2 - 3x – xy + 3y

= x(x - 3) - y(x - 3) 

= (x - 3) (x – y) 


2. How to factorize by grouping the following expressions?

(i) 2x4 – x3 + 4x - 2

Solution:

2x4 – x3 + 4x - 2

= x3(2x – 1) + 2(2x - 1)

= (2x – 1) (x3 + 2)

(ii) pr + qr - ps - qs

Solution: 

  pr + qr - ps - qs

= r(p + q) - s(p + q)

= (p + q) (r - s)

(iii) mx - my - nx - ny

Solution: 

mx - my - nx - ny

= m(x - y) - n(x - y)

= (x - y) (m - n)

 

3. How to factorize by grouping the algebraic expressions?

(i) a2c2 + acd + abc + bd

Solution:

a2c2 + acd + abc + bd

= ac(ac + d) + b(ac + d)

= (ac + d) (ac + b)


(ii) 5a + ab + 5b + b2

Solution:

5a + ab + 5b + b2

= a(5 + b) + b(5 + b)

= (5 + b) (a + b)


(iii) ab - by - ay + y2

Solution:

ab - by - ay + y2

= b(a - y) - y(a - y)

= (a - y) (b - y)

4. Factorize the expressions:

(i) x4 + x3 + 2x + 2

Solution:

x4 + x3 + 2x + 2

= x3(x + 1) + 2 (x + 1)

= (x + 1) (x3 + 2)


(ii) f2x2 + g2x2 – ag2 – af2

Solution:

f2x2 + g2x2 – ag2 – af2

= x2(f2 + g2) – a (g2 + f2)

= x2(f2 + g2) – a(f2 + g2)

= (f2 + g2)(x2 – a)



5. Factorize by grouping the terms (a2 + 3a)2 - 2(a2 + 3a) – b(a2 + 3a) + 2b

Solution:

(a2 + 3a)2 - 2(a2 + 3a) – b(a2 + 3a) + 2b

= [(a2 + 3a)2 - 2(a2 + 3a)] – [b(a2 + 3a) - 2b]

= (a2 + 3a) (a2 + 3a - 2) – b(a2 + 3a - 2)

= (a2 + 3a - 2) (a2 + 3a - b)





8th Grade Math Practice

From Factorize by Grouping The Terms to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.